The pharmacokinetics and pharmacodynamics of esomeprazole in sheep after intravenous dosing - Smith, Joe S.; Gebert, Jessica; Bennett, Kailee; Ebner, Lisa Sams; Flynn, Ryan; Mulon, Pierre-Yves; Harvill, Lainey; Escher, Olivia Grace; Kreuder, Amanda Jo; Bergman, Joan; Cox, Sherry (Frontiers in Veterinary Science, 2023)
Abomasal (gastric) ulceration is a morbidity in sheep, and currently, there is a paucity of pharmacokinetic and pharmacodynamic data for gastroprotectant drugs reported for this species. The proton pump inhibitor esomeprazole has been used in small animal and human patients for gastroprotection via increasing the gastric pH. The objective of this study was to report the pharmacokinetic parameters and pharmacodynamic effect of esomeprazole in sheep after single intravenous dosing. Four healthy adult Southdown cross ewes had blood collected over a 24 hour time period after single intravenous dosing of esomeprazole at 1.0 mg/kg. Abomasal fluid was sampled over 24 hours before and after esomeprazole administration. Plasma samples were analyzed for concentrations of esomeprazole and the esomeprazole metabolite, esomeprazole sulfone by high performance liquid chromatography. Pharmacokinetic and pharmacodynamic data were evaluated with specialized software. Esomeprazole was rapidly eliminated after IV administration. Elimination half-life, area under the curve, initial concentration (C0), and clearance were 0.2 hr, 1197 hr*ng/mL, 4321 ng/mL, and 0.83 mL/hr/kg, respectively. For the sulfone metabolite elimination half-life, area under the curve and maximum concentration were 0.16 hr, 22.5 hr*ng/mL, and 65.0 ng/mL, respectively. Abomasal pH was significantly elevated from 1-6 hr after administration and remained above 4.0 for at least eight hours after administration. No adverse effects were noted in these sheep. Esomeprazole was rapidly eliminated in sheep, similar to goats. Abomasal pH was increased, but future studies will be necessary to develop a clinical management approach to the use of esomeprazole in sheep.